Bridging text and reality: The principles of Tadabbur from An-Nabulsi's perspective in modern tafsir studies - Ridwan, Ali; Zulaiha, Eni (UIN Sunan Gunung Djati Bandung, 2025)
This study deeply examines the principles of Tadabbur (contemplation) of Surat Al-Baqarah in Muhammad Ratib An-Nabulsi's exegesis,